Association between aortic and intracranial aneurysms (ATAAC Study) - Tom Le Corvec, MD, PhD; Romain Bourcier, MD, PhD; Matilde Karakachoff, MSc; Pacôme Constant dit Beaufils, MD, MSc; Hubert Desal, MD, PhD; Jean-Michel Serfaty, MD, PhD; Guillaume Guimbretière, MD, MSc; Blandine Maurel, MD, PhD (JVS-Vascular Insights)
Objective: Aortic aneurysms (AAs) and intracranial aneurysms (IAs) are two serious conditions that occur together in 7.2% and 11.8% of cases, respectively. The aim of this study was to find common risk factors between AAs and IAs that could be used for targeted screening of combined disease. Methods: Retrospective data were collected from consecutive patients with a combined condition (AA + IA, target group, taken from our Biomedical Data Warehouse from 2012 to 2020) and compared with two control groups: a first control group of patients operated on for an AA without IA (taken from a prospectively maintained database) and a second control group of patients with IA only (taken from the national ICAN database). Univariate and multivariate analyses were performed to compare the target group with each control group. Results: We included 67 patients with combined disease, 153 with isolated AA and 128 with isolated IA. In patients with AA, the patient characteristics associated with an increased risk of also having IA were peripheral arterial occlusive disease (odds ratio [OR], 3.02; P = .007) and multiple sites of AA (OR, 2.97; P = .002). Among patients with an IA, the following characteristics were associated with an increased risk of also having an AA: hypertension (OR, 3.28; P = .0005), coronary artery disease (OR, 12.07; P < .0001), and peripheral artery disease (OR, 4.14; P = .0001). The location of IA in the anterior communicating artery tended to lead to an increased risk of having AA (OR, 1.92; P = .09). Conclusions: This pilot study identifies several characteristics that could be used to select patients at risk for a combined aneurysmal disease (AAs and IAs) for screening. A prospective study is required to confirm these data.